Обґрунтування вибору мови моделювання бізнес-процесів для системи управління виробництвом на базі платформи DELMIA APRISO - Штих, С. В. (ХНУРЕ, 2023)
Business process modeling is essential for understanding and improving an organization's activities. By constantly improving their processes, organizations can remain competitive in the market and meet changing customer needs. The DELMIA Apriso platform is applied to the manufacturing execution system (MES) to improve production processes by providing real-time visibility, control, and monitoring of manufacturing operations. To understand and effectively deploy the system, a business process model reflecting the state of business processes is required, and its language should fully reflect the components and systems of the DELMIA Apriso platform.
Keywords: моделювання бізнес-процесів; платформа DELMIA Apriso; система управління виробництвом